Effects of a manganese oxide-modified biochar composite on adsorption of arsenic in red soil. (1st November 2015) - Yu, Zhihong; Zhou, Li; Huang, Yifan; Song, Zhengguo; Qiu, Weiwen
Abstract: The arsenic adsorption capacity of a manganese oxide-modified biochar composite (MBC), prepared by pyrolysis of a mixture of potassium permanganate and biochar, was investigated in red soil. Adsorption experiments using batch procedures were used to estimate the arsenic adsorption capacities of the absorbent materials. Adsorption and desorption isotherms, Fourier-transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS) were used to characterise the prepared adsorbent materials, and a plausible mechanism for arsenic removal by MBC was proposed. Arsenic in red soil–MBC mixtures exhibited lower mobility than that in soils amended with pristine biochar. The improved removal performance of soil–MBC mixtures was attributed to a lower H/C ratio, higher O/C ratio, higher surface hydrophilicity, and higher surface sorption capacity, even though the impregnation of manganese oxide decreased the specific surface area of the biochar. Arsenic retention increased as the biochar content increased, mainly owing to an increase in soil pH. Several oxygenated functional groups, especially O–H, CO, Mn–O, and Si–O, participated in the adsorption process, and manganese oxides played a significant role in the oxidation of arsenic. This study highlights the potential of MBC as an absorbent to immobilise arsenic for use in contaminated land remediation in the red soils region. Highlights: Manganese oxide modified-biochar composite (MBC) can enhance the adsorption of arsenic in red soil. MBC can potentially be used as an absorbent to remediate arsenic contaminated soils. A possible mechanism involving partial oxidation of As (III) to As (V) by manganese oxides is proposed.